Sarcoidosis of the breasts – when should it be considered? A case report - Jaguś Dominika; Yafimtsau Ivan; Mlosek Robert K.; Jonczak Luiza; Roszkowska-Purska Katarzyna; Dobruch-Sobczak Katarzyna (Journal of Ultrasonography, 2022)
Sarcoidosis is a systemic inflammatory disease of unknown aetiology. Given its complex clinical presentation, the disorder frequently causes diagnostic challenges. In most cases, the primary manifestation is in the lungs and mediastinum. Breast involvement as the primary manifestation of sarcoidosis is rare, accounting for less than 1% of cases. The authors present the case of a 44-year-old woman whose disease first manifested as multiple non-specific BIRADS 4 lesions in both breasts, accompanied by axillary lymphadenopathy, detected by ultrasound examination. The lesions were not visible on mammography. The course of the disease was clinically silent, with intermittent remissions, until the complete resolution of focal breast lesions on ultrasound after two years of follow-up. The paper presents an algorithm for the management of multifocal breast pathology with associated lymphadenopathy, which led to the prompt verification of sarcoidosis.